2024
DOI: 10.3390/w16040571
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Soil Water Retention and Water Content in Retrogressive Thaw Slumps in the Qinghai-Tibet Plateau, China

Haitao Sun,
Pei Wang,
Yuhua Xing
et al.

Abstract: Retrogressive thaw slumps (RTSs) are becoming more common on the Qinghai-Tibet Plateau as permafrost thaws, but the hydraulic properties of thaw slumps have not been extensively studied. To fill this knowledge gap, we used the “space-for-time substitution method” to differentiate three stages of RTSs: original grassland, collapsing, and collapsed. Our study included on-site investigations, measurements in the laboratory, and measured and simulated analyses of soil water retention curves and estimated hydrologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Andrenelli et al [15] found higher porosity and lower bulk density, but Lim et al [16] observed an increase in saturated hydraulic conductivity, and Major et al [17] discovered no effect on biochar. An increase in soil retention capacity was observed by Sun et al [18] and Nguyen et al [19]. Contrary, a decrease or no effect, was found by Kameyama et al [20].…”
Section: Introductionmentioning
confidence: 88%
“…Andrenelli et al [15] found higher porosity and lower bulk density, but Lim et al [16] observed an increase in saturated hydraulic conductivity, and Major et al [17] discovered no effect on biochar. An increase in soil retention capacity was observed by Sun et al [18] and Nguyen et al [19]. Contrary, a decrease or no effect, was found by Kameyama et al [20].…”
Section: Introductionmentioning
confidence: 88%